CHANGES IN HEMATOLOGICAL PARAMETERS IN AUTOIMMUNE HEMOLYTIC ANEMIA - Kurbonova Z.Ch.,; Khushbokova G.U., (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2026)
Relevance: Although the primary focus in AIHA is on erythrocyte destruction, changes in the leukocyte formula are of significant clinical importance for assessing the course, severity, and pathogenetic background of the disease.Material and methods: A study was conducted on 50 patients diagnosed with AIHA at the multidisciplinary clinic of TTA. The patients were divided into three groups based on the duration of the disease: Group I — 20 patients (up to 6 months), Group II — 18 patients (from 6 months to 2 years), and Group III — 12 patients (from 2 to 4 years). The control group consisted of 10 healthy individuals.Results: Analysis of the leukocyte formula showed that the neutrophil count was 68.23±3.22% in Group I, 64.08±4.54% in Group II, and 62.65±2.85% in Group III, showing no significant difference compared to the control group (65.35±3.85%). The relative proportions of lymphocytes (Lim), monocytes (Mon), eosinophils (Eoz), and basophils (Bas) in all patient groups were also similar to the control group values, with no statistically significant differences identified (p > 0.05). These results indicate that the primary pathogenetic changes in autoimmune hemolytic anemia leave the leukocyte lineage relatively intact.